Conditions for Using Means of Emphasis from The Point Of View Of Grammar and Stylistics - Mullasadikova Nigora Miramonovna (Penerbit Jurnal Indonesia, 2024)
Knowledge of the subtle features of the language plays an important role in improving the efficiency of speech. There are three types of sentences in Arabic, depending on the situation of the listener. The expected results from these types of offers are also considered to be different. Usually the speaker distinguishes the type of speech he uses based on the situation of the listener. A speaker who seeks to convince the listener in his speech must know how to enhance the content of speech. Depending on the situation of the listener, it is determined how many means of assertion can be used in a sentence. There are more than 50 types of them in Arabic. One of them is considered to be an amplifying application. In this article, the author reflects on the concept of amplification and its types, as well as the features in its use. At the same time, he comments on the concept of amplification and its application in Arabic. He explains the opinions of classical scholars on this issue mainly on the basis of Qur'anic verses.